Evaluation of engineering training curricula for compliance with didactic principles of STEAM education: - Джантасова, Дамира; Ахметова, Динара; Калинин, Алексей; Юрченко, Василий (Pedagogy and Psychology, 2022)
The article deals with the issue of training programs evaluation and learning outcomes through the STEAM education methodology. The determination of measures to develop the innovative training of technical specialist’s potential through the Art component in STEM is carried out through the use of classification and comparative analysis methods in order to determine ways to integrate the theory and practice of art into other sciences. The didactic provisions of STEAM approach in higher education are derived on the basis of a multivariate SWOT analysis of STEAM learning models in the educational process of the technical university. This study was carried out during the implementation of the project "Developing the potential for innovative training of engineers through STEAM education", approved by the priority "Research in education and science" for 2021-2023. with the financial support of the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan (Grant No. АР09260338). The authors propose a definition of the concept of “STEAM education” in terms of training technical personnel, present the purpose, scientific methods and potential of the project, consider the main directions for the development of this process within the framework of personal and foreign research experience in building training programs using the STEAM approach.